Strategies For Developing Women’s Entrepreneurship in The MSMEs Sector: A Systematic Literature Review - Awalia, Riska; Syarief, Rizal; Haryati, Teti (School of Business, IPB University (SB-IPB), 2025)
Background: The increase in the number of women entrepreneurs in Indonesia reflects progress in gender participation in business, particularly in the MSME sector, which is heavily occupied by women entrepreneurs. MSMEs themselves are a crucial pillar in Indonesia's economy. However, many barriers and challenges still need to be addressed for women’s entrepreneurship to reach a higher level.Purpose: This study seeks to examine the growth of women’s entrepreneurship within the MSME sector, identify the shortcomings and challenges encountered by women entrepreneurs, and determine the strategies necessary to enhance their effectiveness.Design/methodology/approach: The research method uses a systematic literature review (SLR) of 20 studies related to women entrepreneurs in the MSME sector.Findings/Result: The findings show that while women entrepreneurs can sustain themselves through various economic conditions, there are significant weaknesses, particularly in financial management and marketing.Conclusion: This study concludes that implementing a comprehensive strategy and policies, including education and training in entrepreneurship, enhancing marketing support, leveraging technology and e-commerce, improving financial literacy, increasing access to capital, and creating stronger social networks, will help balance personal and professional responsibilities.Originality/value (state of the art): This study uniquely and specifically addresses women’s entrepreneurship, which plays a key role in Indonesia’s economy, particularly in the MSME sector that is often overlooked. Researching women’s entrepreneurship can provide significant contributions to both academics and practitioners in enhancing the sustainability and performance of women while tackling various challenges in business. Keywords: women entrepreneurship, MSMEs, challenges, strategies, systematic literature review (SLR)